Upcycling post-harvest biomass residues from native European Lupinus species: from straws and pod shells production to nutritive value and alkaloids content for ruminant animals - Maia, Margarida R. G.; Monteiro, André; Valente, Inês M.; Sousa, Carla; Miranda, Carla; Castro, Carlos; Cortez, Paulo P.; Cabrita, Ana R. J.; Trindade, Henrique; Fonseca, António J. M. (Frontiers in Nutrition, 2023)
The production of Lupinus seeds for food and feed is increasing worldwide, which results in large amounts of post-harvest biomass residues, considered of low value and left in the field to be burned or incorporated in the soil. To valorize these agricultural wastes, this work aimed to assess their potential as an alternative feed for ruminants. Thus, the production yield, nutritive value, and alkaloid content of straws and pod shells from three native European Lupinus species, L. albus ‘Estoril’ (white), L. angustifolius ‘Tango’ (narrow-leafed), and L. luteus ‘Cardiga’ (yellow), cultivated in two locations, were evaluated. The dry matter (DM) yield of straws and pod shells were the highest for L. albus ‘Estoril’ (4.10 t ha-1) and the lowest for L. angustifolius ‘Tango’ (1.78 t ha-1), suggesting a poor adaptation of narrow-leafed lupin to the particularly dry and warm agronomic year. Despite species-specific differences, lupin biomass residues presented higher crude protein (53.0-68.9 g kg-1 DM) and lignin (103-111 g kg-1 DM) content than cereal straws usually used in ruminant feeding, thus resulting in higher metabolizable energy (6.43-6.58 MJ kg-1 DM) content. In vitro digestibility was similar among lupin species (47.7-50.6%) and higher in pod shells (53.7%) than in straws (44.6%). Lupinus albus ‘Estoril’ and L. luteus ‘Cardiga’ presented considerable amounts of alkaloids in straws (23.9 and 119 mg kg-1 DM) and pod shells (20.5 and 298 mg kg-1 DM), while no alkaloids were detected in L. angustifolius ‘Tango’ biomass residues. Considering the combined production of straw and pod shells per lupin species, it is anticipated that lupin biomass residues produced per ha can fulfill 85% of the energy and nearly 50% of protein requirements of a flock of 4 to 9 dry and mid-pregnancy sheep with 50 kg body weight for one year. No negative effects on small (ovine) and large (bovine) ruminant species due to alkaloids are expected, even if biomass residues are consumed at up to 85% DM intake. The large production yield along with its nutritive value unveils the potential of lupin biomass residues valorization as alternative fodder for ruminants, promoting sustainability under a circular economy approach.